The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jrs.5999
|View full text |Cite
|
Sign up to set email alerts
|

228‐nm quadrupled quasi‐three‐level Nd:GdVO4 laser for ultraviolet resonance Raman spectroscopy of explosives and biological molecules

Abstract: We describe a new compact diode-pumped solid-state frequency quadrupled quasi-three-level neodymium-doped gadolinium vanadate (Nd:GdVO 4) laser that generates $50 mW of 228-nm quasi-continuous wave light as ns pulses at a tunable kilohertz repetition rate. We developed two generations of this laser. The first generation has a high duty cycle and a tunable repetition rate. The second generation is optimized for maximum output power. We utilize these new lasers to measure ultraviolet resonance Raman (UVRR) spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…We described this new laser elsewhere. 18 The 228 nm Raman excitation overlaps with the π→π* electronic transitions associated with conjugated double bonds, aromatic rings, amides, NO x compounds, and other DUV chromophores.…”
Section: Deep-ultraviolet Lasermentioning
confidence: 99%
“…We described this new laser elsewhere. 18 The 228 nm Raman excitation overlaps with the π→π* electronic transitions associated with conjugated double bonds, aromatic rings, amides, NO x compounds, and other DUV chromophores.…”
Section: Deep-ultraviolet Lasermentioning
confidence: 99%
“…One way of achieving ~228 nm lasers is the quadruple-frequency conversion of either the 914 nm output of Nd:YVO4 crystal, or 912 nm output of Nd:GdVO4 crystal. Sergei V. Bykov et al [17] reported acousto-optically Q-Switched, frequency quadrupled 912 nm Nd:GdVO4 laser with the average output power of 30 mW. Nd:YVO4 and Nd:GdVO4 have some advantages in common, including high absorption cross section, broad absorption bandwidth and polarization output.…”
Section: Introductionmentioning
confidence: 99%